Detection of a Borrelia sp. from Ixodes granulatus Ticks Collected from Rodents in Malaysia - Khoo, Jing Jing; Ishak, Siti Nabilah; Lim, Fang Shiang; Mohd-Taib, Farah Shafawati; Khor, Chee Sieng; Loong, Shih Keng; AbuBakar, Sazaly (Journal of medical entomology, 2018)
The Borrelia genus consists of spirochete bacteria known to cause Lyme disease (LD) and relapsing fever in humans. Borrelia pathogens are commonly transmitted via arthropod vectors such as ticks, mites, or lice. Here, we report the molecular screening of LD group Borrelia sp. from ticks (Acari: Ixodidae) collected from rodents trapped in recreational forests and a semiurban residential area in the Selangor state in Malaysia. Of 156 adult ticks surveyed, 72 ticks were determined as positive for Borrelia sp. by polymerase chain reaction (PCR). All Borrelia PCR-positive ticks belonged to the Ixodes granulatus Supino species. Borrelia sp. was not detected in other tick species examined, including Dermacentor sp. and Amblyomma sp. ticks. Thirteen Borrelia PCR-positive tick samples were selected for further sequence analyses. Phylogenetic analyses of partial flaB gene sequences revealed that the Borrelia sp. were closely related to the LD group borreliae, Borrelia yangtzensis; a novel Borrelia genospecies reported in East Asian countries including Japan, Taiwan, and China. To our knowledge, this is the first report of Borrelia sp. related to Borrelia yangtzensis detected in Malaysia and Southeast Asia. The zoonotic potential of the Borrelia sp. reported here merits further investigation, as it may explain the previously reported serological evidence for borrelial infections in Malaysia.